Cardioprotective effects of dronedarone mediated by the influence on the expression of urokinase-type plasminogen activator receptor - Becher, Tobias; Seiler, Lea; Rudic, Boris; Röger, Susanne; Tueluemen, Erol; Liebe, Volker; Kuschyk, Jürgen; Trinkmann, Frederik; Michels-Zetsche, Julia D.; Weiß, Christel; Akın, Ibrahim; Kälsch, Thorsten; et al. (Journal of vascular research, 2019)
Purpose: Dronedarone is a multichannel-blocking antiarrhythmic drug for the treatment of atrial fibrillation. Observational data hypothesized a cardioprotective effect. In an in vitro endothelial cell-platelet model, we evaluated the molecular atheroprotective effects of dronedarone. Methods: Following a 24-h incubation of human umbilical vein endothelial cells (HUVECs) with dronedarone (concentration 50, 100, and 150 ng/mL), they were then stimulated for 1 h with lipopolysaccharide (LPS) and were subsequently incubated in direct contact with thrombin-activated platelets. After incubation, the expression of CD40L and CD62P on platelets, and the expression of ICAM-1, VCAM-1, urokinase-type plasminogen activator receptor (uPAR), and membrane type 1 matrix metalloproteinase (MT1-MMP) on endothelial cells were measured by flow cytometry. Results: Preincubation with 150 ng/mL of dronedarone reduced the expression of uPAR on endothelial cells after proinflammatory stimulation with LPS and also by direct endothelial contact with activated platelets (p = 0.0038). In contrast, the expression of CD40L and CD62P on platelets after proinflammatory stimulation with thrombin was significantly increased through direct preincubation with 50/100/150 ng/mL of dronedarone. However, dronedarone had no effects on the expression of MT1-MMP and ICAM-1 in HUVECs. Conclusion: In this in vitro analysis, dronedarone directly increased platelet activation but showed significant direct effects on endothelial cells and indirect effects on platelets on selected markers of atherosclerosis.
Gesehen am 18.11.2019